The impact of credit on the economic development of Brazilian states (2002–2019) - Festa Júnior, José Carlos; Mikael, Lucas (Revista Economia Ensaios, 2024)
This study examines the intersection between credit and economic development in Brazil, focusing on regional disparities. Using a robust methodology and updated data, the findings reveal that the unequal distribution of credit significantly impacts growth, particularly in the North, Northeast, and Central-West regions, which rely more on short-term credit. The banks' preference for liquidity contributes to credit rationing, with regions having more developed banking systems being less affected. The study emphasizes the need for tailored strategies in credit and regional development policies and suggests future research should incorporate longitudinal approaches and international comparative analyses.